The comparison between the length of vertical dimension of occlusion and the length of thumb on undergraduate Mongoloid students - Teng, Goh Li; Subrata, Gantini; Ardan, Rachman (Padjadjaran Journal of Dentistry, 2011)
The Thumb Rule of Leonardo da Vinci states that many proportions of the face show relationship with the length of thumb which is measured from the proximal tip of the proximal phalanx to the distal tip of the distal phalanx. Previous studies have shown that the length of the vertical dimension of occlusion (VDO) is similar to the length of thumb of the Caucasoid race. The purpose of this study is to determine whether the length of VDO have correlations with the length of thumb among those of the Mongoloid race. This study took a survey method with the analytical cross-sectional approach. A total of 80 students of Faculty of Dentistry who have fulfilled all population criteria were randomly chosen to measure the length of VDO and the length of the thumb. Results analyzed with Student's t-test statistic revealed that there was a significant difference between males and females in the length of VDO and the length of the thumb, however, there was no significant difference between the length of VDO and the length of the thumb. There were very strong correlations (P<0.05) between the length of VDO and the length of the thumb. As a conclusion, the length of thumb can be suggested as an objective method to determine the length of VDO in this population.